Genetics of susceptibility to leishmaniasis in mice: four novel loci and functional heterogeneity of gene effects - Havelková, H; Badalová, J; Svobodová, M; Vojtíková, J; Kurey, I; Vladimirov, V; Demant, P; Lipoldová, M (Genes and immunity, 2006)
Symptoms of human leishmaniasis range from subclinical to extensive systemic disease with splenomegaly, hepatomegaly, skin lesions, anemia and hyperglobulinemia, but the basis of this variation is unknown. Association of progression of the disease with Th2 lymphocyte response was reported in mice but not in humans. As most genetic studies in Leishmania major (L. major)-infected mice were restricted to skin lesions, we analyzed the symptomatology of leishmaniasis in mice by monitoring skin lesions, hepatomegaly, splenomegaly and seven immunological parameters. We detected and mapped 17 Leishmania major response (Lmr) gene loci that control the symptoms of infection. Surprisingly, the individual Lmr loci control 13 different combinations of pathological and immunological symptoms. Seven loci control both pathological and immunological parameters, 10 influence immunological parameters only. Moreover, the genetics of clinical symptoms is also very heterogeneous: loci Lmr13 and Lmr4 determine skin lesions only, Lmr5 and Lmr10 skin lesions and splenomegaly, Lmr14 and Lmr3 splenomegaly and hepatomegaly, Lmr3 (weakly) skin lesions, and Lmr15 hepatomegaly only. Only two immunological parameters, IgE and interferon-gamma serum levels, correlate partly with clinical manifestations. These findings extend the paradigm for the genetics of host response to infection to include numerous genes, each controlling a different set of organ-specific and systemic effects.
Keywords: Chromosome Mapping; Genetic Predisposition to Disease; Interferon-gamma; chromozomy; Immunoglobulin E; hepatomegalie; Hepatomegaly; Leishmaniasis; interferon gama; kůže; Animals; Chromosomes; Leishmania major; mapování chromozomů; Skin; zvířata; imunoglobulin E; myši; inbrední kmeny myší; leishmanióza; splenomegalie; Mice; Mice, Inbred Strains; genetická predispozice k nemoci; Splenomegaly